Literasi Keuangan dan Pilihan Investasi Masyarakat Aceh - Nisa, Khairan; Hidayat, Muhammad Rahmat (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study examines the relationship between financial knowledge and attitudes towards finance with individual financial behavior within the framework of the Lacanian perspective. The research defines financial knowledge as the symbolic dimension of an individual's mind encompassing concepts of finance, investment, and debt management. Attitudes towards finance are described as the imaginative aspect of an individual's personality involving views, preferences, and emotions related to money and financial management. Utilizing a statistical analysis approach, the study uncovers a significant correlation between financial knowledge, attitudes towards finance, and financial behavior. However, the research outcomes must be interpreted cautiously due to potential confirmation bias and heuristic effects in data interpretation. Managerial implications of this study involve the development of financial education programs aimed at shaping prudent and responsible financial behavior.